The Impact of Emotional Intelligence on The Professional Judgment of External Auditors in Saudi Arabia - Al-Juaid, Atheer Khalaf Owid; Al-Sudairi, Fahdah Sultan (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aims to determine the extent to which emotional intelligence affects the professional judgment of external auditors in Saudi Arabia. The study followed the traditional methodology by employing a positive theory that depends on explaining, interpreting, and predicting a specific phenomenon by reviewing the previous literature and linking it to reality; and then formulating the questions and hypotheses that represent the axes on which the study is based. Accordingly, Accordingly, this questionnaire designed and was directed at a random sample of 152 external auditors from the study community consisting of external auditors working in audit offices in Saudi Arabia year 2023-2024.  The study concluded that there is a direct relationship between the role of the emotional intelligence of the external auditor and the professional judgment of the external auditor, which classifies the strength of the relationship as a weak relationship. She also concluded that there is a direct relationship between the role of the emotional intelligence of the external auditor and the good management of time pressure, work pressure, feeling pressure, and emotions. This study recommends that audit offices pay attention to emotional intelligence skills by training employees, to cope with pressures faced by auditors within the office and while performing audit work. It also recommends that external auditors be further educated in how colleagues within the audit office and office clients work and establish and maintain good working relationships. In addition to training auditors to organize their work time and make sure to implement it without procrastination. Finally, prioritizing business and starting the most important then the important, and developing and improving the work environment.
Keywords: emotional intelligence; professional judgment; time pressure; work pressure; feeling and emotional pressure; audit